Organic electronic ratchets doing work - Roeling, Erik M.; Germs, Wijnand Chr.; Smalbrugge, Barry; Geluk, Erik Jan; Vries, Tjibbe de; Janssen, René A. J.; Kemerink, Martijn (Nature materials, 2011)
Ratchet systems can extract work from non-equilibrium processes. Yet present electronic ratchets only operate at cryogenic temperatures and generate low currents, which are clear limitations for their practical use. Now, organic electronic ratchets providing enough power to drive simple logic circuits at room temperature have been realized.